Social policies in poverty reduction and improvement of social welfare in Bolivia - Ramos Menar, Braulio (2017)
Social policies have contributed significantly to the development and economic growth processes in the countries and the improvement of social welfare. In Bolivia, these policies have been implemented in times of crisis and economic stability, the goal of the policies were aimed at reducing poverty. This article aims to study the various social policies that occurred in the period 1980 -2016, in relation to the conditional transfer programs implemented in Bolivia. To do this, we use a review of the specialized literature and the available documents and reports, so the research includes a qualitative and interpretive analysis. The main results are gathered with special emphasis on the achievements and scope of the policies in the national territory, and finally highlights the importance of social policies as elements or mechanisms that have accompanied the new configuration of the Bolivian state.